Clinical experience with intravenous and oral formulations of the novel histone deacetylase inhibitor suberoylanilide hydroxamic acid in heavily pretreated patients with hematological malignancies (Hematology Meeting Reports, 2009)
HDACIs are a novel class of anti-cancer drugs whose primary mechanism of action revolves around altering chromatin structure, and subsequently, gene expression. At present, there are several classes of compounds that have been identified that inhibit HDACs and cause transformed cell growth arrest, differentiation and/or apoptosis. These compounds have been shown to inhibit the activity of partially purified HDACs and to inhibit the growth of several types of cancers in tumor bearing models. Alterations in histone acetyl transferases (HATs) have been reported in several types of cancer, as genes encoding HATS have been translocated, amplified, over-expressed and or mutated in different malignancies. Conversely, specific alterations in HDACs have not been reported in cancer, though HDACs are known to be associated with oncogenes and tumor suppressor genes.